2016
DOI: 10.14444/3034
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent disc height reduction and clinical outcome after intradiscal cement leakage

Abstract: Intradiscal cement leakage was associated with the degeneration of cement-containing disc but did not reduce the clinical efficacy at early stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In addition to osteoporosis, excessive balloon distraction during surgery and multiple levels surgery, intradiscal leakage could be an independent risk factor for adjacent fractures. In the meantime, many studies revealed that bone cement may be toxic to the intervertebral disc and that it accelerates degeneration [49][50][51]. In our study, despite the higher intradiscal leakage rate, we did not observe a higher rate of adjacent segment fractures in the high-viscosity cement group.…”
Section: Discussioncontrasting
confidence: 69%
“…In addition to osteoporosis, excessive balloon distraction during surgery and multiple levels surgery, intradiscal leakage could be an independent risk factor for adjacent fractures. In the meantime, many studies revealed that bone cement may be toxic to the intervertebral disc and that it accelerates degeneration [49][50][51]. In our study, despite the higher intradiscal leakage rate, we did not observe a higher rate of adjacent segment fractures in the high-viscosity cement group.…”
Section: Discussioncontrasting
confidence: 69%
“…They reported that at a mean follow-up of 20.56 months, intradiscal cement leakage was associated with a significant reduction in disc heights, without influencing clinical efficacy. 20 Our study also did not look at the risk factors for cement leakage during kyphoplasty. Ren et al studied the correlative factors for complications resulting from cement leakage in 71 patients who had kyphoplasty.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the clinical implications of the intervertebral disc degeneration were not evaluated. This issue has been examined in a recent study by Shen et al, 20 who compared 20 patients who had an intradiscal leak with 104 patients who did not. They reported that at a mean follow-up of 20.56 months, intradiscal cement leakage was associated with a significant reduction in disc heights, without influencing clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…On comparing pre- and post-operative intervertebral disc height differences between the experimental and control groups, all p-values were more than 0.05, indicating that PKP does not lead to significant changes in the height of the intervertebral discs. However, Shen M et al reported that intradiscal cement leakage can cause intervertebral disc degeneration [ 31 ]. Another study by Salamat S et al [ 21 ] reported that a Pfirrmann score of grade 5 is linked to significantly lower quantitative disc height scores.…”
Section: Discussionmentioning
confidence: 99%